Harnessing protest potential: Russian strategic culture and the colored revolutions. Issue 4 (1st October 2020) - German, Tracey
ABSTRACT: The perceived threat posed to Russia from so-called colored revolutions–popular uprisings attributed by Moscow to malign sponsorship by external forces–has become a central theme in Russian security discourse. This article analyses how colored revolutions came to be characterized as a specific threat to national security and how they continue to shape Russian thinking about the changing character of conflict. It explores Russian perceptions of the threat from colored revolutions, using the concept of strategic culture as a framework to analyze these perceptions through an analysis of the Russian military theoretical literature and strategic documents. The article establishes that concerns about non-military means of destabilization reflect continuities in Russian strategic assumptions about adversaries and how they seek to achieve their national objectives. It also reveals the perpetuation of specific narratives about the country's vulnerability to foreign interference.